Effect of physical training on bone mineral density in prepubertal girls: a comparative study between impact-loading and non-impact-loading sports - Courteix, D.; Lespessailles, E.; Peres, S. L.; Obert, P.; Germain, P.; Benhamou, C. L. (Osteoporosis International, 1998)
Physical activity is known to have an anabolic effect on bone tissue. It has been shown to increase the bone mineral density (BMD) in young adults, as well as in teenagers. But there is little information about the effect of intensive physical activity in childhood, particularly at the prepubertal stage. To examine the influence of an early intensive physical training on BMD, we have studied a group of elite prepubertal girls, at the starting phase of their peak bone mass acquisition. Subjects were engaged either in sport requiring significant impact loading on the skeleton, or in sport without impact loading. Forty-one healthy prepubertal girls took part in this study. The sport group consisted of 10 swimmers (10.5 +/- 1.4 years old) and 18 gymnasts (10.4 +/- 1.3 years old), who had performed 3 years of high-level sport training (8-12 h per week for swimmers, 10-15 h per week for gymnasts). Thirteen girls (10.7 +/- 1 years old) doing less than 3 h per week of physical activity served as a control group. BMD measurements were done using dual-energy X-ray absorptiometry. There was no statistical significant difference between groups as regards age, body height and weight, and body composition. There was no statistical significant difference between swimmers and controls for all the BMD measurements. Mean BMD in gymnasts was statistically higher than in the control group for mid-radius (+15.5%, p < 0.001), distal radius (+33%, p < 0.001), L2-4 vertebrae (+11%, p < 0.05), femoral neck (+15%, p < 0.001) and Ward's triangle (+15%, p < 0.01). Moreover, in gymnasts, BMD at radius, trochanter and femoral neck was above normative values. We conclude that physical activity in childhood could be an important factor in bone mineral acquisition in prepubertal girls, but only if the sport can induce bone strains during a long-term program: gymnastics has such characteristics, unlike swimming. Such acquisition could provide protection against risks of osteoporosis in later life, but this remains debatable.